International Comparison of Demand for Imports - Chang, Tse Chun (Review of Economic Studies, 1945)
Journal Article International Comparison of Demand for Imports Get access Tse Chun Chang Tse Chun Chang Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 13, Issue 2, 1945, Pages 53–67, https://doi.org/10.2307/2296036 Published: 01 September 1945